Management Factors Influencing the Management of the Happy Workplace for Police Stations in Thailand - Sudsakorn, Tawit (Asian Interdisciplinary and Sustainability Review, 2019)
This research paper aims to study the happiness levels in accordance with the “Happy Workplace” principles by the Thai Health Promotion Foundation for police stations in Thailand, and to investigate the causal influences of management factors on the happy workplace management of police stations in Thailand. This research is a quantitative research, based on data collected from 380 samples from the target population of 1,671 commissioned and non-commissioned police officers who have participated in the prototype happy workplace project previously conducted in nine police stations around the country by Sudsakorn et al. (2017). The results from the data analyses indicated that: (1) under eight levels of happiness in Happy Workplace principles, the happiness level of the police stations in Thailand was found to be highest at the “Happy Heart” (kind-hearted; considerate) level, followed by the “Happy Soul” (good spirit) and “Happy Society” (good society), respectively; “Happy Money” was scored lowest, reflecting the fact that even though Thai police officers are working under financial limitations, insufficient budget and operational resources, they still manage to work cooperatively and sacrifice their personal happiness for their work; and (2) the management factors that have the most positive and significant influences on happiness in police stations are organizing and leading. The two other factors, planning and controlling, however, have insignificant influences on happiness.